Manjón, educator - Arce García, Victorino de (Pulso. Revista de educación, 2002)
Through this article, I aim to demonstrate that Andrés Manjón is among the most exceptional educators of his time, and he should even be considered the forerunner of the New School movement. He introduced the concept of the Open-Air School or School of the Ave Maria. I also attempt to clarify certain misconceptions regarding the origin and purpose of the Ave Maria Schools, which were established by Manjón. I address questions such as whether these schools were limited to being "Neighbourhood schools” and whether his students were exclusively gypsies. The information presented in this article is based on the authority of the most prestigious experts such as Manjón’s work. Additionally, I would like to pay homage by sharing the tribute written by the son of one of his first collaborators, who was also my father.